Protective efficacy of statins in patients with Klebsiella pneumoniae bloodstream infection - Xu, Qian; Zheng, Beiwen; Shen, Ping; Xiao, Yonghong (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Patients with bloodstream infection of Klebsiella pneumoniae (BSI-KP) have a high risk of death and septic shock. This study aims to identify the risk factors for mortality and severity in patients of BSI-KP. Methods: Data of BSI-KP patients were extracted from the MIMIC IV database, and patients infected with only K. pneumoniae in blood were included in this study. The risk factors of 28-day mortality and septic shock in BSI-KP patients were analyzed, respectively. Results: A total of 279 patients enrolled and the all-cause 28-day mortality rate was 11.8%. The use of statins (OR 0.220, 95% CI 0.060-0.801, p = 0.022) and quinolones (OR 0.356, 95% CI 0.143-0.887, p = 0.027) were both independent protective factors for death within 28 days, while the use of vasoactive drugs (OR 7.377, 95% CI 1.775-30.651, p = 0.006) was a risk factor. Besides, pulmonary disease (OR 2.348, 95% CI 1.126-4.897, p = 0.023), bleeding and coagulation disorders (OR 3.626, 95% CI 1.783-7.372, p < 0.001), respiratory failure (OR 2.823, 95% CI 0.178-6.767, p = 0.020) and kidney dysfunction (OR 2.450, 95% CI 1.189-5.047, p = 0.015) were independent risk factors for patients suffered from septic shock while hypertension was a protective one. The receiver operating characteristic (ROC) curves could well predict the risk of death within 28-day (area under ROC = 0.855, 95% CI = 0.796–0.914, p < 0.001) and septic shock (AUROC = 0.815, 95% CI = 0.755–0.874, p < 0.001) in patients with BSI-KP. Conclusion: The use of statins could decrease the risk of 28-day mortality in patients of BSI-KP. The risk factor-based prediction model provided evidence for drug treatment in BSI-KP patients. Paying more attention to the strategy of treatment will be an optimal way to improve patient’s outcome in clinical practice.